Smoking Cessation, Weight Change, and Risk of Parkinson's Disease: Analysis of National Cohort Data - Kim, Ryul (J Clin Neurol, 2020)
BACKGROUND AND PURPOSE: To determine whether the postcessation weight gain modifies the protective effect of smoking on the development of Parkinson's disease (PD). METHODS: This nationwide cohort study included 3,908,687 Korean males aged ≥40 years who underwent at least 2 health checkups biennially between 2009 and 2015. They were grouped into current smokers; quitters with body mass index (BMI) increase, maintenance, and decrease; and never smokers. The occurrence of incident PD was tracked, and Cox proportional-hazard models were used to adjust for potential confounding factors. We also analyzed the impact of weight change regardless of smoking status in the study population. RESULTS: There were 6,871 incident PD cases observed during the 13,059,208 person-years of follow-up. The overall risk of PD was significantly lower in quitters than in never smokers [hazard ratio (HR)=0.78, 95% confidence interval (CI)=0.70–0.86]. The risk of PD was still lower in quitters with BMI increase (HR=0.80, 95% CI=0.65–0.98) and in those with BMI maintenance (HR=0.77, 95% CI=0.68–0.87). This tendency was also observed in quitters with BMI decrease (HR=0.76, 95% CI=0.55–1.06), although it was not as robust as in the other two groups. With respect to weight change alone, BMI increase (HR=1.10, 95% CI=1.02–1.18) but not BMI decrease (HR=1.06, 95% CI=0.98–1.14) significantly increased the PD risk compared to BMI maintenance. CONCLUSIONS: Postcessation weight gain in males did not offset the protective impact of smoking on PD development, although overall weight gain predicted an increased risk of PD.